2015
DOI: 10.1108/aeds-02-2014-0005
|View full text |Cite
|
Sign up to set email alerts
|

Link education to industrial upgrading: a comparison between South Korea and China

Abstract: Purpose – Why is the “education to industrial innovation” equation not working in China? Why has education development contributed to South Korea’s success but not promoted technology development and industrial upgrading in China? The purpose of this paper is to compare South Korea and China and try to address that puzzle. The author will also identify which mediating factors are crucial in linking education development to industrial innovation and industrial upgrading. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 43 publications
0
12
0
4
Order By: Relevance
“…Fourth, none of the indicators of HEO contributes to industrial structure upgrading, partly due to the lack of effective channels between HEO and ISE. In addition, as revealed by He [5] higher education itself is not a sufficient condition for industrial structure upgrading, since other intermediating markets and social contexts are crucial too, especially the rational allocation of educational resources to both the private and public sectors, rather than one or the other. Thus, to advance the industrial structure, it is crucial to develop a friendly and fair environment and optimise the resources between different sectors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Fourth, none of the indicators of HEO contributes to industrial structure upgrading, partly due to the lack of effective channels between HEO and ISE. In addition, as revealed by He [5] higher education itself is not a sufficient condition for industrial structure upgrading, since other intermediating markets and social contexts are crucial too, especially the rational allocation of educational resources to both the private and public sectors, rather than one or the other. Thus, to advance the industrial structure, it is crucial to develop a friendly and fair environment and optimise the resources between different sectors.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, scholars have highlighted the importance of higher education for ISE, and have demonstrated that higher education can accelerate ISE through knowledge spillovers, technological innovations, and entrepreneurial ecosystems [18,19]. He [5] and OECD [9] claimed that a large pool of creative human capital is crucial for making such approaches possible; this capital tends to include masters and doctoral students. Some empirical examples confirming the above-mentioned viewpoints focus on South Korea, Hong Kong, Singapore, Taiwan, and Japan, all of which, through massive investments in higher education, have realized industrial upgrading and a successful transformation from low-value-added exportation to high-value-added exportation [20].…”
Section: The Relationship Between Higher Education and Economic Develmentioning
confidence: 99%
See 3 more Smart Citations